A review of very large vapour cloud explosions: Cloud formation and explosion severity. (July 2017) - Atkinson, Graham; Cowpe, Edmund; Halliday, Julie; Painter, David
Abstract: This paper presents a review of Vapour Cloud Explosions (VCEs) to examine: 1. The relationship between weather conditions, source term and development of the flammable cloud. 2. The consequences of explosion in clouds with higher reactivity than methane. The review identified that sustained small leaks in low wind conditions are associated with very large clouds and higher likelihood of ignition leading to a severe VCE. The examination of primary data from several LPG and gasoline incident investigations showed that in many cases severe overpressure effects extended to a high proportion of the cloud: damage was not confined to areas where there was congested pipework or vegetation. The analysis also suggests that radiation effects may be the key to understanding the explosion mechanism in many incidents. The paper concludes with a discussion of how the new data on vapour cloud explosions that has become available over the last ten years may affect risk assessment and emergency planning in the future. Highlights: A majority of very large vapour cloud incidents occurred in nil or very low wind conditions. Most serious vapour cloud incidents were relatively small but sustained leaks. Severe overpressure effects were generally not confined to congested areas. All of the very large (R > 200 m, T > 300s) gasoline clouds reviewed produced severe explosions - not flash fires. Thermal radiation effects may be the key to understanding the explosion mechanism in many incidents.